Super-Oxidized Solution Nebulization for the Symptomatic Treatment of Airway Infections Including COVID-19 Cases Report - Rebollar González, Dr. Roberto Carlos; López, Dr. Edgar Torres (International Journal of Innovative Research in Medical Science, 2020)
The coronavirus SARS CoV2 pandemic has had a great impact worldwide due to the disease contagious high degree and its range of clinical manifestations, from a mild to a severe condition that can end in death. The main transmission of the virus is by drops produced by coughing, sneezing, or talking that reach the host's airways. The initial location of the virus is in the nostrils and oropharynx during the first days of infection (viral phase); later it descends to the lower airway (pulmonary phase) where it can manifest itself in a more aggressive clinical condition. Until now, there is not treatment for this disease. This case series describes a proposal topical viricidal treatment in the respiratory tract by directly nebulized electrified super-oxidized solution (SOS). Thirty-two patients with epidemiological, clinical or imaging criteria for COVID-19 disease were included. The average age was 48.8 years, male sex 65%, comorbidities 46% (diabetes mellitus, high blood pressure and obesity). Confirmatory test (SARS-CoV2 in oropharynx 6 and IgM 2) was obtained in 8 subjects. The average time of treatment started since onset of symptoms was 2.7(SD±1.8) days. No deaths or hospital admissions were reported. The average symptoms duration after treatment begun was 12.5(SD±2) days. Before treatment starting, average respiratory rate (RR) was 22.6(SD±2.3) breaths per min (bpm) and average saturation of oxygen (SO2) was 85(SD±6.5)%. Two days after starting treatment, a SO2 gradual increase was observed, as well as a RR gradual decrease. A 70% of subjects achieved > 93% SO2 from day 8, and 100% reached RR <24 bpm at 4th day. From day 2, a decrease and amelioration in incidence and grade of discomfort was observed in practically all symptoms reaching less than 25% incidence of symptoms and on a scale of 2 to 4 at 10th day. The adverse effects (AE) associated with nebulization did not require treatment or suspend its application; less than 50% of cases reported headache, cough exacerbation, and dyspnea (more common AE). This case series proposes that nebulized SOS treatment improve a bad evolution (stops the deterioration of SO2 and RR) and improves the symptomatology of the COVID-19 disease.